A new genus and three new species of Neotropical Tanyproctini (Coleoptera: Scarabaeidae: Melolonthinae) - Neita, Jhon Cesar; Ocampo, Federico C. (Zootaxa, 2012)
A new genus of scarab beetle, Eideria Neita & Ocampo, and three new species, E. pentaphylla Neita & Ocampo, E. glabripenisNeita & Ocampo, and E. pedroantonioi Neita & Ocampo, are described based on specimens collected in the drylands ofColombia and rainforests of Ecuador. Based on the evaluation of morphological characters and within the context of the currentclassification of the subfamily Melolonthinae, this genus is placed in the tribe Tanyproctini (formerly called Pachydemini).Diagnostic characters, illustrations, and an identification key are provided for the new species. The relationships of Eideria with other Neotropical Tanyproctini genera are discussed.